PENGHINDARAN PAJAK DI INDONESIA: PENGARUHTRANSFER PRICING DAN CUSTOMER CONCENTRATIONDIMODERASI OLEH PERAN KOMISARIS INDEPENDEN - Bella Yohana (2021)
This study aims to examine and analyze the effect of transfer pricing, costumer concentration on tax avoidance and the effect of transfer pricing, costumer concentration with independent commissioners as a moderating variables. The sample in this study is 112 samples came from 40 non-financial companies are listed on Indonesian Stock Exchange (BEI) in 2017-2019. This study is a quantitative research using random effect model. The sampling technique used purposive sampling method and Multiple Linear Regression as the analysis technique. Testing the hypothesis using STATA version 13 analysis tool with a significant level of 0.05%. The result of data analysis indicate that (1) transfer pricing had positive significant effect, (2) customer concentration had negative significant effect on tax avoidance, and (3) Independent commissioner not weaken or strengthen transfer pricing and customer concentration on tax avoidance. Keywords: tax avoidance; transfer pricing; customer consentration; independent commissioner